2018
DOI: 10.1148/radiol.2018171361
|View full text |Cite
|
Sign up to set email alerts
|

Digital Breast Tomosynthesis and Synthetic 2D Mammography versus Digital Mammography: Evaluation in a Population-based Screening Program

Abstract: Purpose To compare the performance of digital breast tomosynthesis (DBT) and two-dimensional synthetic mammography (SM) with that of digital mammography (DM) in a population-based mammographic screening program. Materials and Methods In this prospective cohort study, data from 37 185 women screened with DBT and SM and from 61 742 women screened with DM as part of a population-based screening program in 2014 and 2015 were included. Early performance measures, including recall rate due to abnormal mammographic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 22 publications
5
80
0
5
Order By: Relevance
“…A potential solution may lie in the use of synthetic imaging, which provides the generation of a synthesised 2D image from DBT data (and thus eliminating the use of 2Dmammography), and is available from some manufacturers. There are on-going studies on the use of synthetic imaging in screening [40][41][42][43] and the identification of its strengths and weaknesses [44].…”
Section: Discussionmentioning
confidence: 99%
“…A potential solution may lie in the use of synthetic imaging, which provides the generation of a synthesised 2D image from DBT data (and thus eliminating the use of 2Dmammography), and is available from some manufacturers. There are on-going studies on the use of synthetic imaging in screening [40][41][42][43] and the identification of its strengths and weaknesses [44].…”
Section: Discussionmentioning
confidence: 99%
“…Digital breast tomosynthesis (DBT) is being increasingly used in clinical practice given that it increases cancer detection rate [1][2][3][4][5], reduces recall rate [2,3,6,7], and improves overall diagnostic accuracy [6,8]. DBT increases conspicuity of lesions and allows for identification of lesions that may be occult or observed only retrospectively on digital mammography (DM), such as architectural distortion.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…More recently, Aujero et al found no significant difference in DCIS detection rates in their community practice when switching from FFDM plus DBT to SM plus DBT (26). Population screening results comparing SM plus DBT to conventional digital mammography found an increase in DCIS detection with SM plus DBT versus conventional digital mammography (27). These more recent study results suggest that SM may be sufficient to detect clinically significant microcalcifications.…”
Section: Amorphous Microcalcifications (Dcis Missed By One Reader)mentioning
confidence: 95%